The effect of amaranth oil on proteinuria in lupus prone mice - Martirosyan, Danik; Hutcheson, Jack; Sajitharan, Deena; Williams, Samantha; Mohan, Chandra (Functional Food Science, 2021)
Background: Kidney disease is a leading cause of death in the United States and the world. Proteinuria signifies kidney damage and can exacerbate kidney disease. It has become an important indicator of kidney disease; reducing proteinuria results in renoprotective effects and slows renal disease. Existing treatments do not work for every patient.Aim of Study: Amaranth is a tropical plant that was regularly consumed in the ancient Central American diet. It has a plethora of health effects and is a strong functional food candidate. This study examines whether a regular oral dose of amaranth oil decreased proteinuria concentration in murine subjects. Methods: Mice in the experimental group (n = 3) were given 4μl of amaranth oil per gram of mouse weight for 5 days a week over 84 days. Control mice (n = 2) were sham treated on the same schedule with no oil. Urine protein concentration was determined by Bradford assay, measuring absorbance at 595nm, then comparing with a BSA standard curve. Results: The experimental group showed decreased proteinuria levels throughout the entire 84 days of studyConclusion: Results show amaranth oil may help decrease proteinuria levels in lupus prone murine subjects. Given the small sample size, the data are preliminary. More research is needed to validate the results and determine the optimal dose and treatment schedule.Key words: proteinuria, amaranth oil, renoprotective, kidney disease, renal disease, lupus, functional food